Darunavir–cobicistat–emtricitabine–tenofovir alafenamide: safety and efficacy of a protease inhibitor in the modern era - Squillace N; Bozzi G; Colella E; Gori A; Bandera A (Dove Medical Press, 2018)
Nicola Squillace,1 Giorgio Bozzi,2 Elisa Colella,1 Andrea Gori,2 Alessandra Bandera1 1Infectious Diseases Unit, Azienda Socio Sanitaria Territoriale di Monza, San Gerardo Hospital, University of Milano-Bicocca, Monza, Italy; 2Infectious Disease Unit, Department of Internal Medicine, Fondazione IRCCS Ca’Granda, Ospedale Maggiore Policlinico, Department of Pathophysiology and Transplantation, University of Milano, Milan, Italy Abstract: A fixed-dose combination consisting of darunavir (Drv), cobicistat (Cobi), emtricitabine (2',3'-dideoxy-5-fluoro-3'-thiacytidine [FTC]), and tenofovir alafenamide (Taf) has been recently approved by the European Medicines Agency for the treatment of HIV infection, and is the first ever protease-inhibitor-based single-tablet regimen. This article provides a detailed description of its pharmacokinetic, efficacy, and safety profile. The pharmacokinetics of single compounds were analyzed, with a special focus on contrasts between Drv/Cobi and Drv/ritonavir (Rtv). When comparing Cobi and Rtv, multiple interactions must be taken into account: in comparison to Rtv, Cobi is a more selective CYP3A4 inhibitor and has no clinical effect on other isoenzymes inhibited by Rtv (eg, 2C8 and 2C9). Moreover, unlike Cobi, Rtv shows in vivo induction activity on some CYP isoenzymes (eg, 1A2, 2C19, 2C8, 2C9, and 2B6), glucuronyltransferases (eg, UGT1A4), and Pgp. Drv-Cobi-FTC-Taf has recently been demonstrated to be of equal efficacy to Drv-Rtv and other protease inhibitors in both experienced (EMERALD study) and naïve (AMBER study) patients. Moreover, kidney and bone safety profiles have been shown to be good, as has central nervous system tolerance. Total cholesterol:low-density-lipoprotein cholesterol and total cholesterol:high-density-lipoprotein cholesterol ratios are generally high in Drv-Cobi-FTC-Taf vs Rtv-Drv-FTC + tenofovir disoproxil fumarate. An unlikely role of Drv in influencing cardiovascular risk in HIV infection has also been reported. Kidney safety profile is influenced by Cobi, with an increase in creatinine plasma concentration of 0.05–0.1 mg/dL and a parallel glomerular filtration-rate reduction of 10 mL/min within the first 4 weeks after Cobi introduction, which remains stable during treatment. Bone and central nervous system safety profiles were found to be good in randomized clinical trials of both experienced and naïve patients. The efficacy and safety of Drv/Cobi/FTC/Taf are comparable to other drug regimens recommended for HIV treatment. Keywords: protease inhibitors, darunavir/cobicistat, emtricitabine/tenofovir alafenamide, HIV